A Survey of risk for developing dementia in community dwelling elderly in Chiang Mai and Lampoon - Munkhetvit, Peeraya; Rattakorn, Phuanjai; Sasat, Daranee; Phadsri, Supaluck; Punyanon, Therapat; Apikomonkon, Hataichanok Apikomonkon (Journal of Associated Medical Sciences, 2017)
Background: With increasing number of elderly people in Thailand, the number of elderly at risk of dementia is increased accordingly. Prevalence of dementia for those living in community is needed information for health promotion and prevention of dementia. Objectives: To investigate prevalence of dementia in elderly community dwellers living in Chiang Mai and Lampoon. Materisls and methods: Montreal Cognitive Assessment (MoCA), Thai version was used as a tool. Five communities including Maekha, San Kamphaeng, Sanklang, Nong Kaeo, Nong Khwai and Ma Kok were explored. One hundred and seventy six elderly persons participated in the study. Results: It was shown that 95.4% of participants were at risk for dementia. The prevalence reported from Maekha, Sanklang and Nong Kaeo were 97.7&, 96.7&% and 91.9%, respectively where Nong Khwai and Ma Kok were similar of 95.2%. Conclusion: All in all, there is a high prevalence of dementia in these community